(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This study is essentially anexperimental study where a between-subject design was employed. Unlike someprevious advertising research (e.g. Kim and Biocca, 1997) utilizing existingadverts, specifically design adverts were made for the study. Standardized 10minute film clips were used to induce a negative or positive mood. Two scales -attitude towards using advertised products and intention to try advertisedproducts - were employed to measure advertising effectiveness. The resultrevealed that subjects in the induced positive mood group have a more positive attitude and greater intention to try advertised products whencompared with subjects in the induced negative mood group. This suggests that advertisers should present adverts in a context that elicitshappiness’.